A Successful Bisphosphonates Monotherapy in Spinal Form of Paediatric Chronic Recurrent Multifocal Osteomyelitis (CRMO)—Case Report - Aleksandra Opala; Jagoda Hofman; Michał Hutny; Aleksandra Wylazlowska; Paweł Matusik (Metabolites, 2023)
Chronic recurrent multifocal osteomyelitis (CRMO) is a non-infectious inflammatory disorder resulting from the multifocal bone and bone marrow lesions with periodic relapses and remissions and with an uncertain prognosis. Treatment options in CRMO are based on expert opinion and relatively small groups of patients. A nine-year-old female patient with no significant past medical history presented with compression fractures and multifocal bone lesions in the thoracic and lumbar spine, as shown in imaging (CT, MRI). Densitometry revealed a diffuse decrease in bone density. Based on the patient’s clinical image and above examinations, the other possible aetiologies—infectious (including tuberculosis), neoplasms, Langerhans cell histiocytosis—were ruled out, which led to eventual final diagnosis—CRMO. The patient was successfully treated with pamidronate infusion initiated in cycles over three consecutive days every 3 months. In addition to clinical improvement, there was a significant remission of inflammation and bone structure healing assessed by MRI after four treatment cycles. Intravenous bisphosphonates usage seems to be a good therapeutic option in CRMO paediatric patients with spinal localization of the lesions complicated by compressive fractures. However, more data, based on larger patient populations, are needed to provide a detailed paediatric CRMO treatment algorithm.